Dynamical Analysis of a Nonlinear Financial System with Computational Algebra Methods - Orhan Ozgur Aybar (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
Thispaper presents algebraic invariants and bifurcation analysis of a nonlinearfinancial system. We focus on the local stability of the equilibrium points ofthis system and find the suitable values of parameters for Hopf Bifurcation.Finally, we investigate the invariants to show the general behaviour.